"Why bother?": Barriers to reporting gender and sexual harassment in emergency medicine. (5th July 2022) - Zeidan, Amy; Patel, Jasmyne; Dys, Gabrielle; Dean, Laura; Curt, Alexa; Lin, Michelle P.; Samuels‐Kalow, Margaret
Abstract: Background: Gender and sexual harassment in emergency medicine (EM) is persistent in the workplace but remains underreported. Barriers to reporting in EM are largely unknown. This study explored barriers to reporting gender and sexual harassment among EM faculty and residents and potential improvements to reporting systems. Methods: We conducted semistructured interviews with EM faculty and residents across the United States, utilizing purposive sampling to ensure diverse representation. All interviews were recorded, transcribed, and coded by two independent investigators. Interviews were conducted until thematic saturation and prominent themes were identified from coded data. Results: A total of 32 interviews were completed with women and men faculty and residents. Prominent themes were identified representing compounding barriers to reporting. Participants described confusion over what constitutes a reportable definition of gender and sexual harassment, unfamiliarity with reporting processes, and multiple avenues (both informal and formal through departmental, hospital, and institutional systems) for reporting. Participants expressed limited confidence in formal reporting systems and related several perceived and actual negative outcomes of reporting. A number of improvements were recommended centering around creating reporting systems that supported, empowered, and protected survivors; improving transparency about reporting processes; and ensuring accountability at a departmental and institutional level. Conclusions: Significant barriers to reporting exist and deter individuals from reporting. Given the negative consequences of ongoing gender and sexual harassment, emergency departments and institutions must take responsibility to reduce barriers and support individuals throughout the reporting process.